2005
DOI: 10.1007/s00228-005-0031-9
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of oral antihyperglycemic drugs over a 7–year period (1998–2004) in a Hungarian population and adherence to drug therapy

Abstract: The utilization pattern of OAHDs considerably changed, but there were no significant changes in patients' adherence. The significant increase in the utilization of OAHDs is not the result of increased adherence but of increased patient number.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 13 publications
2
21
0
2
Order By: Relevance
“…Our results regarding other medical and demographic factors confirmed associations observed in IBIS including age and risk of breast cancer. STAR, as well as several studies regarding adjuvant tamoxifen therapy and other medications, found greater persistence or adherence for older patients 5,6,31,34-37 although inverse or U-shaped associations have also been observed. 3,38 Veronesi reported that breast cancer patients taking tamoxifen in an adjuvant therapy trial were more likely to adhere than were women in a chemoprevention trial, which is consistent with our observation that higher perceived health risk increases adherence.…”
Section: Discussionmentioning
confidence: 92%
“…Our results regarding other medical and demographic factors confirmed associations observed in IBIS including age and risk of breast cancer. STAR, as well as several studies regarding adjuvant tamoxifen therapy and other medications, found greater persistence or adherence for older patients 5,6,31,34-37 although inverse or U-shaped associations have also been observed. 3,38 Veronesi reported that breast cancer patients taking tamoxifen in an adjuvant therapy trial were more likely to adhere than were women in a chemoprevention trial, which is consistent with our observation that higher perceived health risk increases adherence.…”
Section: Discussionmentioning
confidence: 92%
“…Satisfactory refill adherence was defined as dispensed refills covering 100 ± 20% of the prescribed treatment time. This range (80–120%) is commonly used in adherence research (24, 29). A refill adherence of 100% equals the amount of drugs that would last for the entire prescribed treatment time.…”
Section: Methodsmentioning
confidence: 99%
“…In the logistic regression analysis, satisfactory refill adherence and oversupply were grouped together as ‘satisfactory refill adherence’ being compared with ‘undersupply’. In the literature, many studies do not indicate an upper level of refill adherence (24), as oversupply is more difficult to interpret than satisfactory refill adherence and undersupply. Therefore, only satisfactory refill adherence and undersupply are reported.…”
Section: Methodsmentioning
confidence: 99%
“…Further, because irregular and inconsistent intake of one or more drugs in a polypharmacy regimen is common and may impact on clinical outcomes, assessment of adherence to polypharmacy is clinically relevant. The few studies that have attempted to calculate adherence to several concurrent medications have averaged the indices obtained for each of the single-medications [1115]. This method has been shown to overestimate [16] but may also underestimate adherence to polypharmacy regimens.…”
Section: Introductionmentioning
confidence: 99%